Measuring Effect of Stress Test Scenario on the Efficiency of Banks in the UK - Chhaya, Khevna Prashant (2015)
Abstract In 2014, the Bank of England on recommendation from the Financial Policy Committee carried out the UK variant of stress test. Eight major banks in the UK namely Barclays, the Co- operative Bank, HSBC, Lloyds Banking Group, Nationwide Building Society, Royal Bank of Scotland, Standard Charter and Santander UK were included in the stress test owing to their systematic importance in the sector. While all the banks except Co- operative bank were found to be capital adequate, the Bank of England stress test did not include the efficiency level of these banks under the stress scenario. As the smooth running of any economy largely depends on the efficiency of its financial institutions, especially banks, it becomes imperative to check if the banks in UK would continue to remain cost efficiency under stress scenario. Thus, the present study uses Stochastic Frontier Analysis (SFA) Approach to compare the level of cost x- efficiency of banks in the UK when stress scenario is introduced to the macro economic variables. The empirical results suggest that although there is a minor decrease in the level of cost x- efficiency of banks under adverse macroeconomic conditions, there is no major threat to the efficient working of banks overall. In other words, banks in the UK were found to be fairly efficient and resilient to the stress in environmental variables.